A influência do colecionismo na representação da memória social: análise da coleção Amidicis Tocantins - Santos, Admeire da Silva [UNESP] (2015)
The Mato Grosso Federal University Central Library counts with a collection of rare and special works that receives the collector's name: Coleção Amidicis Tocantins - CAT. The collector, a common man, who liked to collect social relevant books, died and left the collection under the care of his family which decided to donate the collection. The donation process was intermediated by the family members and the Mato Grosso Federal University rector who in the period showed interest in receiving the collection. The Central Library, as many others Brazilian public universities, struggles with financial problems to give proper treatment to the collection, be it structural or of personal capacitation.This way the works that belong to the collection don't have any treatment, which has been causing many questioning s. And the question here worked is: Can a previously particular collection represent a collective memory? In the search for the resolution of this question it was ranked as the main objective to identify and discuss the relevance of an institutionalized collection in the configuration of social memory, in the Information Science scope, through the studying of the Amidicis Tocantins Collection case. In this sequence it is aimed to analyze, in the Information Science scope, the terms collection, object, memory and place of memory, establishing, there for, a dialogue between these concepts; to analyze in loco the Amidicis Tocantins Collection in order to collect information and to interpret, through the literature, the questions pertinent to the collection's meaning and finality; to present how the Amidicis Tocantins Collection can represent a social memory and reflect the motives for which it was chosen by the institution. The works methodology is a case study in which has been utilized the theoretical proposition to analyze the data displaced in an analytical form and text.The Amidicis Tocantins Collection was analyzed in the ...